Quality Awareness and Its Influence on the Evaluation of App Meta-Information by Physicians: Validation Study - Albrecht, Urs-Vito; Framke, Theodor; von Jan, Ute (JMIR Publications, 2019)
BackgroundMeta-information provided about health apps on app stores is often the only readily available source of quality-related information before installation. ObjectiveThe purpose of this study was to assess whether physicians deem a predefined set of quality principles as relevant for health apps; whether they are able to identify corresponding information in a given sample of app descriptions; and whether, and how, this facilitates their informed usage decisions. MethodsAll members of the German Society for Internal Medicine were invited by email to participate in an anonymous online survey over a 6-week period. Participants were randomly assigned one app description focusing on cardiology or pulmonology. In the survey, participants were asked three times about whether the assigned description sufficed for a usage decision: they were asked (1) after giving an appraisal of the relevance of nine predefined app quality principles, (2) after determining whether the descriptions covered the quality principles, and (3) after they assessed the availability of detailed quality information by means of 25 additional key questions. Tests for significance of changes in their decisions between assessments 1 and 2, and between assessments 2 and 3, were conducted with the McNemar-Bowker test of symmetry. The effect size represents the discordant proportion ratio sum as a quotient of the test statistics of the Bowker test and the number of observation units. The significance level was set to alpha=.05 with a power of 1-beta=.95. ResultsA total of 441 of 724 participants (60.9%) who started the survey fully completed the questionnaires and were included in the evaluation. The participants predominantly rated the specified nine quality principles as important for their decision (approximately 80%-99% of ratings). However, apart from the practicality criterion, information provided in the app descriptions was lacking for both groups (approximately 51%-92%). Reassessment of the apps led to more critical assessments among both groups. After having familiarized themselves with the nine quality principles, approximately one-third of the participants (group A: 63/220, 28.6%; group B: 62/221, 28.1%) came to more critical usage decisions in a statistically significant manner (McNemar-Bowker test, groups A and B: P<.001). After a subsequent reassessment with 25 key questions, critical appraisals further increased, although not in a statistically significant manner (McNemar-Bowker, group A: P=.13; group B: P=.05). ConclusionsSensitizing physicians to the topic of quality principles via questions about attitudes toward established quality principles, and letting them apply these principles to app descriptions, lead to more critical appraisals of the sufficiency of the information they provided. Even working with only nine generic criteria was sufficient to bring about the majority of decision changes. This may lay the foundation for aiding physicians in their app-related decision processes, without unduly taking up their valuable time.